Fabrication of hierarchically structured supercapacitor using N and S codoped activated carbons derived from Samanea saman biomass - Sarmah,S; Kakati,BK; Kucernak,ARJ; Deka,D (Energy Storage, 2024)
Biomass-derived activated carbons have emerged as highly promising electrode materials for electrochemical supercapacitors due to their remarkable characteristics, such as high surface area, cost-effectiveness, and environmental sustainability. This study focuses on the synthesis of N and S co-doped activated carbons (NSACs) from Samanea saman (rain tree) biomass through a combined hydrothermal-chemical activation process. Leveraging the advantageous hierarchical structure inherent to biological sources, the resulting NSACs demonstrate enhanced ion transport, leading to remarkable capacity and power density. The NSACs synthesized by pyrolysis at 800°C exhibit exceptional specific capacitances of 434 and 401 Fg−1 in Na2SO4 and H2SO4 electrolytes, respectively, in a three-electrode system. The capacitance retention of the same NSAC was found to be 77.6% at a corresponding current density of 10 Ag−1 in H2SO4 electrolyte. This outstanding electrochemical performance can be attributed to the material's high specific surface area (1402 m2 g−1), well-defined hierarchical porous structure, and a substantial degree of graphitization. A symmetric supercapacitor constructed using the synthesized NSACs demonstrates notable energy densities of 14.5 and 25.0 Whkg−1, with H2SO4 and Na2SO4 electrolytes respectively. Furthermore, the symmetric supercapacitor exhibits excellent stability, retaining 91.3%–94.3% of its capacity after 5000 consecutive GCD cycles with H2SO4 and Na2SO4 electrolytes, respectively. The synergistic combination of the unique characteristics of NSACs derived from Samanea saman biomass presents a promising avenue for the development of high-performance and environment-friendly supercapacitors.